Hungary Under Soviet Rule IV: A Survey of Developments from August 1959 to August 1960 - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): American Friends of the Captive Nations Chapters: Soviet Economic Exploitation; Socialist Transformation of Agriculture; Soviet Military Intervention in Hungary 1960; The People's Spiritual Resistance: It is not only peasants who resist; it is also teachers in schools; parents in their homes; the clergy in churches; students in the University, youth on the farms and in the factory and yes, even Communist party members in the privacy of their families. Appendix: Letter by Sir Leslie Munro to the New York Times, 8 August 1960.